2021
DOI: 10.3389/fpsyg.2021.712447
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Expectations and Parental Stress During Emergency Distance Learning and Their Relationship to Students’ Perception

Abstract: School closures in spring 2020 caused by the COVID-19 pandemic were an unprecedented and drastic event for students, parents, and teachers. The unplanned adaptation of classroom instruction to emergency distance learning was necessary to ensure continued education. In this new learning environment, teachers formed expectations for student academic achievement gains, which in turn affected the opportunities for students to learn. Parents faced new challenges in supporting their children’s learning. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 46 publications
(89 reference statements)
0
13
0
1
Order By: Relevance
“…For example, some parents reported being overwhelmed and having problems to motivate their children to study ( Garbe et al, 2020 ). Garrote et al (2021) found a negative association between stress in parents and their children’s online learning experience. Taken together, parents did play a key role for adolescents’ mental health; however, their role may have been more significant with regards to other functions, such as providing emotional security ( Colarossi and Eccles, 2003 ) or providing a daily routine ( Bülow et al, 2021 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…For example, some parents reported being overwhelmed and having problems to motivate their children to study ( Garbe et al, 2020 ). Garrote et al (2021) found a negative association between stress in parents and their children’s online learning experience. Taken together, parents did play a key role for adolescents’ mental health; however, their role may have been more significant with regards to other functions, such as providing emotional security ( Colarossi and Eccles, 2003 ) or providing a daily routine ( Bülow et al, 2021 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
“…With regards to educational challenges, research showed that parents had to take on new unfamiliar roles in home schooling during the COVID-19 school closures, while being more responsible for the educational support of their children (e.g., Garrote et al, 2021 ). Regarding educational concerns in the current study, perceived family support was higher in the resilience profile of adolescents with lower educational concerns and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations